2018
DOI: 10.3389/fnagi.2018.00231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation (tDCS) Over the Frontal Polar Area on Motor and Executive Functions in Parkinson’s Disease; A Pilot Study

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder with motor and non-motor symptoms due to degeneration of dopaminergic neurons. The current pharmacological treatments induce complications associated with long-term use. However, current stimulation techniques for PD treatment, such as deep brain stimulation (DBS), are too invasive. In this context, non-invasive brain stimulation including transcranial direct current stimulation (tDCS) may be a safe and effective alternative treatment for PD. We previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…These findings suggest that the activation of the aPFC is associated with improvement in hand motor functions. Consistent with this idea, our previous studies reported that Oxy-Hb gain in the aPFC positively correlated with performance gain during repeated training in a task similar to the Purdue Pegboard test, and that anodal stimulation of the aPFC by transcranial direct current stimulation (tDCS) increased performance in a motor rehabilitation task similar to the Purdue Pegboard test in healthy adults as well as in patients with Parkinson's disease (Ishikuro et al, 2014(Ishikuro et al, , 2018. Furthermore, activity in the aPFC was reported to correlate with shoulder function after surgery due to shoulder dislocation (Zanchi et al, 2017).…”
Section: Effects Of Neurofeedback Training Targeting the Apfcmentioning
confidence: 65%
See 2 more Smart Citations
“…These findings suggest that the activation of the aPFC is associated with improvement in hand motor functions. Consistent with this idea, our previous studies reported that Oxy-Hb gain in the aPFC positively correlated with performance gain during repeated training in a task similar to the Purdue Pegboard test, and that anodal stimulation of the aPFC by transcranial direct current stimulation (tDCS) increased performance in a motor rehabilitation task similar to the Purdue Pegboard test in healthy adults as well as in patients with Parkinson's disease (Ishikuro et al, 2014(Ishikuro et al, , 2018. Furthermore, activity in the aPFC was reported to correlate with shoulder function after surgery due to shoulder dislocation (Zanchi et al, 2017).…”
Section: Effects Of Neurofeedback Training Targeting the Apfcmentioning
confidence: 65%
“…However, patients with stroke as well as chronic neurological disorders such as Parkinson's disease and Alzheimer's disease are expected to undergo the neurofeedback training, and would be older than the present subjects. A previous study reported that aPFC stimulation by tDCS ameliorated hand dexterity in elder patients with Parkinson's disease (Ishikuro et al, 2018), suggesting that the neurofeedback training to increase aPFC activity might be effective in elder patients. Third, we analyzed relationships between dexterity and hemodynamic activity in the left somatosensory motor-related area, since only this area was activated during the Purdue Pegboard test in the post-assessment session.…”
Section: Limitationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Broeder et al (2019) noted an increase in writing amplitude with anodal tDCS to M1 (1 mA, 20 min). Fregni et al (2006) also noted some benefit in Purdue pegboard task with anodal tDCS to M1 (1 mA, 20 min), but other studies found no significant benefit in dexterity tasks with single-or multi-session tDCS to the fronto-polar area (five sessions, 1 mA, 15 min) (Ishikuro et al, 2018) or DLPFC (10 sessions, 2 mA, 20 min) (Doruk et al, 2014).…”
Section: (B) Effect On Upper Limb Motor Functionmentioning
confidence: 99%
“…• Gait and balance (Benninger et al, 2010;Verheyden et al, 2013;Capecci et al, 2014;Kaski et al, 2014a;Mak and Yu, 2014;Manenti et al, 2014;Valentino et al, 2014;Costa-Ribeiro et al, 2016Schabrun et al, 2016;Swank et al, 2016;Fernandez-Lago et al, 2017;Lattari et al, 2017;Criminger et al, 2018;da Silva et al, 2018;Dagan et al, 2018;Harris et al, 2018;Yotnuengnit et al, 2018;Alizad et al, 2019;Putzolu et al, 2019) • Upper limb function (Fregni et al, 2006;Benninger et al, 2010;Doruk et al, 2014;Salimpour et al, 2015;Costa-Ribeiro et al, 2016;Ferrucci et al, 2016;Schabrun et al, 2016;Cosentino et al, 2017;Ishikuro et al, 2018;Broeder et al, 2019) • Cognition (Nitsche et al, 2005;Boggio et al, 2006;Biundo et al, 2015;Manenti et al, 2016;Elder et al, 2017;Lawrence et al, 2018;Adenzato et al, 2019) • Impulsive pathological gambling behavior (Benussi et al, 2017a) • Speech (Pereira et al, 2013) • Sleep (Hadoush et al, 2018) • Fatigue …”
Section: Mode Of Tesmentioning
confidence: 99%